La evasión tributaria y su impacto en la recaudación fiscal de la agencia de turismo Muyuna Lodge 2024 - Jaen Noriega, Ana Isabel (2025)
The general problem of this study is to determine the impact of tax evasion on the tax collection of the aforementioned agency. To this end, specific objectives were established that seek to analyse the causes of tax evasion and evaluate policies to prevent it. The methodology used was quantitative, non experimental and cross-sectional, with a correlational scope. Structured questionnaires were used to collect data that allowed us to identify that tax evasion generates significant losses in tax collection, limiting the resources available to improve the competitiveness and sustainability of Muyuna Lodge. The conclusions of the study indicate that, although tax policies are in place, they are not sufficient to counteract the structural causes of tax evasion in remote areas such as the Peruvian Amazon. It is recommended to implement joint strategies between the private sector and the government to strengthen infrastructure and foster a culture of tax compliance, thus promoting the development of ecotourism in the region.